The Influence of Shūrā on Decision-Making among Officials of the National Commission on Muslim Filipinos - Rebellion, Lenneth Aidalelynch C.; Malang, Bernandino P.; Malang, Jocelyn DS. (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The study aims to determine the role of the Islamic principle of consultative decision-making, known as Shūrā, in the decision-making processes of the officials of the National Commission on Muslim Filipinos (NCMF). The proponents of this study employed a qualitative method to collect the required information, supporting this study by interviewing six executive and management-level officials of NCMF to gain their perspective on the issue, their practices, and the difficulties encountered in implementing Shūrā. The data were then subjected to thematic analysis using a six-phase data analysis framework developed by Braun and Clarke. The research revealed five primary themes, including: Shūrā as an Islamic and participatory governance value; Shūrā as a form of participatory and consultative decision-making; balancing Islamic consultative values with government procedures; Shūrā as an Organizational Cohesion and Trust value; and the sustainability and institutionalization of Shūrā in NCMF. The findings revealed that Shūrā provides participatory governance, cultivates trust, and bridges Islamic values and formal government processes. However, its continued application relies on making it part of the institution, not just tied to current leaders.